Windows: selected readings in Seventh-day Adventist Church History 1844-1922 - VandeVere, Emmett K. (Southern Publ. Assn., 1975)
Any group that loses a sense of its history, begins to die. to look through the door of the future, one must occasionally glance back through the windows of the past. "Windows" provides such glimpses into the history of the Seventh-day Adventist Church. Dr E K VandeVere has collected together the personal and contemporary accounts of men and women who shaped denominational history. Their words bring the church's story alive, revealing both its turning points and its personal moments.Through letters, diaries, periodical articles, and personal manuscripts, Dr VandeVere lets the pioneers remind us of the Seventh-day Adventist heritage - Millerite Disappointment.Reorientation.Joseph Bates.James White.Ellen White.Sabbath Reform.Adopting a Name and Organizational Structure.Conditional Immortality and the Resurrection.Preachers of the Faith.Expanding Beyond New England.Battle Creek.Church Finances.Health and Seventh-day Adventism.Civil War Worries.Seventh-day Adventists and Worship.Educational Reform.Moments in Missions.Canright.Eighteen Eighty-Eight.The Church at the Turn of the Century.Conflict Over Control.Fires in Battle Creek.Pantheism.Moving Out of Battle Creek.Mrs. White Dies.World War I.Daniells Decades.Index